Routine laboratory tests for staging of cervical cancer. Novel potentialities - N.I. Stuklov; T.V. Sushinskaya; S.V. Epifanova; E.V. Shchepkina; A.I. Kuznetsov (LCC «Medicine-Inform», 2021)
N.I. Stuklov1,2, T.V. Sushinskaya2, S.V. Epifanova3, E.V. Shchepkina4, A.I. Kuznetsov5 1Medical Institute of the Russian University of Peoples' Friendship, Moscow, Russian Federation 2P. Hertsen Moscow Oncology Research Institute - Branch of the National Medical Research Radiological Centre, Moscow, Russian Federation 3Central Clinical Hospital and Polyclinic of the Department for Presidential Affairs, Moscow, Russian Federation 4LLC "Techdepartament", Khimki, Russian Federation 5Moscow Aviation Institute (National Research University), Moscow, Russian Federation Aim: to identify and assess novel potentialities of routine lab tests to improve the accuracy of preoperative staging (spread) of high-grade squamous intraepithelial lesions (HSIL) and cervical cancer (CC). Patients and Methods: 410 women aged 18-82 (median age 42 [34; 51] years) with verified HSIL or CC were enrolled. Women were selected through medical records. Test results were monitored during in-person examinations since the formulation of clinical diagnosis and after surgical staging. If no surgical staging was performed, histopathology and disease stage as established by protocol examinations using instrumental and lab tests were considered. Women were subdivided into groups based on disease stage and method of treatment. Several parameters (complete blood count, hemostasis, biochemical markers of iron metabolism) were measured. In HSIL, minimal mandatory instrumental tests included pelvic and regional lymph node ultrasound. In CC stage 1-4, pelvic and abdominal ultrasound, pelvic MRI, abdominal CT with contrast, and (sometimes) PET CT. Results: several routine parameters of peripheral blood (hemoglobin, RBCs, ESR, fibrinogen, soluble fibrin monomer complexes/SFMC, D-dimer, ADP-induced platelet activation) were identified. Changes in the levels of these parameters within/above/below reference ranges illustrate the systemic effect of malignancy on the body and are a significant marker of regional metastasis of CC undiagnosed during a clinical examination. Conclusion: complex assessment of these parameters in CC allows for suspecting metastasis and requires more careful and reasonable examinations to improve the accuracy of prehospital diagnosis and determine management strategy. Keywords: HSIL, cervical cancer, diagnosis, metastases, hematological markers, hemostasis, peripheral blood parameters, disease stage. For citation: Stuklov N.I., Sushinskaya T.V., Epifanova S.V. et al. Routine laboratory tests for staging of cervical cancer. Novel potentialities. Russian Journal of Woman and Child Health. 2021;4(3):229-237 (in Russ.). DOI: 10.32364/2618-8430-2021-4-3-229-237.